Predictors and preventers of postoperative bedridden status in the elderly ages over 75 after emergency general surgery: a retrospective cohort study - Kantoku Nagakawa; Ken Taniguchi; Aki Yukutake; Yuta Kawaguchi; Ryo Matsumoto; Momoko Akashi; Takanori Hirayama; Masataka Hirabaru; Chika Sakimura; Shigeki Minami; Susumu Eguchi (Acute Medicine & Surgery, 2023)
Aim We investigated the proportion of bedridden patients after emergency surgery among the elderly ages over 75; defined as the latter‐stage elderly in Japan, the associated factors, and interventions used to prevent it. Methods Eighty‐two latter‐stage elderly patients who underwent emergency surgery for non‐traumatic illness between January 2020 and June 2021 in our hospital were included in the study. Backgrounds and various perioperative factors were compared retrospectively between the groups including patients who became bedridden from Performance Status Scale 0 to 3 before admission (Bedridden group) and those who did not (Keep group). Results Three cases of death and seven patients who were bedridden before admission were excluded. The 72 remaining patients were divided into the Bedridden group (n = 10, 13.9%) and the Keep group (n = 62, 86.1%). There were significant differences in the prevalence of dementia, pre‐ and postoperative circulatory dynamics, renal dysfunction, coagulation abnormality, length of stay in the high care unit/intensive care unit, and number of hospital days, with a relative risk of 13 (1.74–96.71), a sensitivity of 1.00, and a specificity of 0.67 for a preoperative shock index of 0.7 or higher being associated with the Bedridden group. Among patients with a preoperative shock index of 0.7 or higher, there was a significant difference in SI at 24 h postoperatively between the two groups. Conclusion Preoperative shock index may be the most sensitive predictor. Early circulatory stabilization seems to be protective against patients becoming bedridden.